ACCESS TO MEDICINE - Ayesha Mustafa; Anam Yasmeen (International Journal of Pharmacy & Integrated Health Sciences)
Availability and access to the health care facility is a fundamental right of human, it is the timely used of services according to the needs. It is included in International treaties and is recognized by authorities and various Governments throughout the world. What does it means the access to medicine? According to WHO (World Health Organization) access to medicines is “having medicines continuously available and affordable at public or private health facilities or medicine outlets that are within one hour’s walk from the homes of the population”. The affordability and availability of medicines is directly related to the strength of health care system, but the high prices of the medicines, prevalence of Non-communicable diseases (diabetes, hypertension) and increasing demand of patients are the major obstacles in this regard. According to Forbes “at least 2 billion people don’t have access to medicines  and 1 billion people live in extreme poverty (less than $1.25 per day) and 2.2 billion live on less than $2 per day which is quite disturbing situation”.  The World Health Organization (WHO) analyzed the global production of pharmaceutical products and it was concluded that 15% of the world’s population consumes over 90% of them. And by World Health Organization it is also estimated that one-third of the developing world population is unable to receive or purchase essential medicine on a regular basis, especially those which are on high demand. The situation is even worst in the under-privileged countries like Africa and Asia, where approximately 50% of the total population does not have sufficient medicines access and healthcare resources and the remaining 50% are using medication incorrectly. However about 10 million lives a year could be saved out of which 4 million in Africa and South-East Asia alone, if we improve the availability, balanced distribution and rational use of medicines. The overall situation of global access to essential medicines is still considered critical. In the privileged countries the budget for healthcare facilities corresponds to 24-66% of National health expenses, which indicates that there is need to monitor the availability and affordability of medicines in these countries. National policies, economical cost of medicine and strategies of procurement are required to ensure the availability of medicines cost-effectively. The people with low income and in-equal health can’t afford costly services of healthcare system.  The policies for the improvement of infrastructure, financing of medical system and the rational use of medicines are formulated and followed on primarily basis. And Governments need reliable information in order to evaluate the impact of policy implementation. In addition to the cost and availability of medicines, it is mandatory to assess the quality of use     and various aspects, such as rational medicine use, adherence of patients and appropriate prescription practices. Thus the access to healthcare system can be made effective, by the assessment of practices in facilities like record reviews and National expert reports. That’s why we are providing healthcare facilities to each person with the help of balanced geographical distribution. The 2016 Index showed that there is moderate progress by the pharmaceutical industries to improve medicines access.  Besides these Pharmaceutical industries should play their role to perk up the medicines access. There is not any particular strategy that suits all systems, but all systems need to promote the provision of new medicinal products, by ensuring medical advancement, improving communication barriers and affordable treatment. And a Reliable Health and Supply system must provide all aspects of health system like procurement, supply and regulation of the medicines.